2010
DOI: 10.1111/j.1600-0633.2010.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Selecting fish‐based metrics responding to human pressures in French natural lakes and reservoirs: towards the development of a fish‐based index (FBI) for French lakes

Abstract: Launois L, Veslot J, Irz P, Argillier C. Selecting fish‐based metrics responding to human pressures in French natural lakes and reservoirs: towards the development of a fish‐based index (FBI) for French lakes. Ecology of Freshwater Fish 2011: 20: 120–132. © 2010 John Wiley & Sons A/S Abstract –  Fish‐based indices of biotic integrity have been developed for many lotic systems but remain scarce for lakes. The goal of this study was to assess the responses of lentic fish assemblages to anthropogenic pressures wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…Since the pioneering work of Karr (1981), fish assemblages have often been used to assess the biological integrity of different water body types Debenay et al, 2003;Oberdorff et al, 2011). However, even if some preliminary indices have been specifically proposed for reservoirs (Blabolil et al, 2016;Launois, Veslot, Irz, & Argillier, 2011;McDonough & Hickman, 1999), such bioindicators are rarely studied in the literature. However, even if some preliminary indices have been specifically proposed for reservoirs (Blabolil et al, 2016;Launois, Veslot, Irz, & Argillier, 2011;McDonough & Hickman, 1999), such bioindicators are rarely studied in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work of Karr (1981), fish assemblages have often been used to assess the biological integrity of different water body types Debenay et al, 2003;Oberdorff et al, 2011). However, even if some preliminary indices have been specifically proposed for reservoirs (Blabolil et al, 2016;Launois, Veslot, Irz, & Argillier, 2011;McDonough & Hickman, 1999), such bioindicators are rarely studied in the literature. However, even if some preliminary indices have been specifically proposed for reservoirs (Blabolil et al, 2016;Launois, Veslot, Irz, & Argillier, 2011;McDonough & Hickman, 1999), such bioindicators are rarely studied in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Non-native introduced species are often large predators such as pikeperch (Sander lucioperca L. 1758) that disturb the structure and dynamics of natural communities (Blanchet et al, 2010;Cucherousset & Olden, 2011;Eby, Roach, Crowder, & Stanford, 2006;Irz, Argillier, & Proteau, 2004). Hence, we can expect (i) a relationship between these non-native species and the functional structure of the whole communities (Mercado-Silva et al, 2009) and (ii) that they interact with eutrophication, which has already been demonstrated to be an important stressor (Blabolil et al, 2016;Launois et al, 2011). As a consequence, these species appear only in some systems and only sporadically.…”
Section: Introductionmentioning
confidence: 99%
“…C'est en particulier le cas en France (Launois et al, 2011 ;Mondy et al, 2012 ;Pont et al, 2006). Par exemple, l'omnivorie est utilisée comme un indicateur de dégradation, alors que la spécialisation dans les habitats de reproduction rend compte d'une altération physique faible du milieu.…”
Section: Une Solution Technique Médiane : Des Indicateurs Se Basant Sunclassified
“…Changes throughout the world are forcing inland fisheries managers to seek new approaches to cope with current and future climates and ecosystem and social challenges (Arlinghaus, Lorenzen, Johnson, Cooke & Cowx, ; Cooke, Arlinghaus, Johnson & Cowx, ; Hunt et al., ). Reservoirs are relatively novel, artificial and heavily modified water bodies with many characteristics and functions that are not comparable to natural lakes and might require different approaches and solutions (Blabolil et al., ; Launois, Veslot, Irz & Argillier, ). The dissimilarity between reservoirs and lakes goes beyond differences in fish fauna development (Kubečka, vs Colby, Spangler, Hurley & McCombie, , respectively) or hydromorphological characteristics (Blabolil et al., ).…”
Section: Introductionmentioning
confidence: 99%